Reaction of the endogenous regulatory mechanisms to early weekday wakeups: a review of its popular explanations in light of model-based simulations - Putilov, Arcady A. (Frontiers in Network Physiology, 2023)
Background: Several widely held explanations of the mechanisms underlying the responses of the endogenous sleep-wake regulating processes to early weekday wake-ups were proposed. Here, they were briefly reviewed and validated against simulations based on the rhythmostatic version of two-process model of sleep-wake regulation. Methods: Simulated sleep times on weekdays and weekends were compared with the times averaged over 1048 samples with either earlier or later weekday risetimes, 74 paired samples collected before and during lockdown, and 93 paired samples collected during early and later school start times. Results: The counterintuitive predictions of the simulations included the following: 1. Just one night of ad lib sleep is sufficient to restore the endogenously determined sleep times after one day/5 days of larger/smaller reduction/extension of the sleep/wake phase of the circadian sleep-wake cycle. 2. Sleep loss on weekdays is irrecoverable. 3. Irrespective of amount of such deadweight loss, sleep on weekends is not prolonged. 4. The control of the circadian clocks over the sleep-wake cyclicity is not disrupted throughout the whole week. Conclusions. The following popular explanations of the gaps between weekends and weekdays in sleep timing and duration were not supported by these simulations: 1. Early weekday wake-ups cause “social jetlag” viewed as the weekend and weekday (back and forth) shifts of the sleep phase relative to the unchanged phase of the circadian clocks. 2. Early weekday wake-ups cause an accumulation of “sleep debt paid back” on weekends, or, in other terms, people can “catch-up” or “compensate” sleep on weekends.